Waterborne Transmission Driving the Prevalence of Blastocystis sp. in Los Ríos Region, Southern Chile - Daniel Sanhueza Teneo; Cedric B. Chesnais; Javiera Manzano; María Paz Moll; Analía Téllez; Guillermo Valenzuela-Nieto (Microorganisms, 2025)
Waterborne gastrointestinal infections remain a global health concern, with approximately 1.7 billion diarrhea-related illnesses annually attributable to protozoan parasites. These pathogens are transmitted through contaminated water and exhibit high resistance to chlorination, posing substantial challenges to effective water treatment. This study focused on the most prevalent intestinal parasites in the Los Ríos Region of Chile: Blastocystis sp., Giardia duodenalis, and Entamoeba coli. The objectives were to assess the prevalence of eukaryotic parasites in water samples—covering both drinking and recreational sources—to describe the circulating subtypes of Blastocystis sp. and to identify ecological factors associated with parasite presence. Water samples were analyzed using conventional PCR, next-generation sequencing (NGS) was employed for Blastocystis sp. subtype identification, and the environmental predictors were evaluated using a multivariable logistic regression model. A total of 132 water samples were analyzed, of which 15.2% were positive for Blastocystis sp. and 1.5% for E. coli, while no samples tested positive for G. duodenalis. We identified subtypes ST1–ST4 of Blastocystis sp., along with ST7, ST10, ST14, ST21, and ST23–ST26, the latter being reported for the first time in Chile. Ecological factors significantly associated with Blastocystis sp. presence included higher water temperature and greater rainfall at positive sites. Potable water was associated with significantly lower odds of Blastocystis sp. infection (aOR = 0.04, 95% CI: 0.00–0.87; p = 0.041), while precipitation increased infection odds by 3% per additional millimeter (aOR = 1.03, 95% CI: 1.00–1.06; p = 0.036). Greater distance to the nearest farmhouse was also significantly associated with reduced infection risk, suggesting that proximity to livestock environments may influence Blastocystis sp. transmission. These findings help explain the high prevalence of Blastocystis sp. observed in humans in the Los Ríos Region and highlight the pivotal role of ecological conditions in driving waterborne transmission. To our knowledge, this is the first environmental study in Chile to clearly demonstrate the association between human infection, environmental factors, and the transmission dynamics of Blastocystis sp.